The skill premium and economic growth with costly investment, complementarities and international trade of intermediate goods - Óscar Afonso (2016)
We analyse the behaviour of the skill premium and the growth rate in an innovator-imitator general equilibrium growth model with international trade of intermediate goods, internal costly investment in both physical capital and R&D, and complementarities between intermediate goods in production. We find that, as opposed to the growth rate, the skill premium is not affected by the complementarities degree nor the investment cost, in any of the countries. We also conclude that, in line with related empirical literature, openness to trade leads to an increase in the skill premium in both countries, while the sign of its impact on the growth rate depends on the magnitude of its counteracting determinants.